Q. 115.0( 1 Vote )

# Evaluate the foll

Formula used:

where,

Here, a = 1 and b = 2

Therefore,

Let,

Here, f(x) = x2 – 1 and a = 1

Now, by putting x = 1 in f(x) we get,

f(1) = 12 – 1 = 1 – 1 = 0

f(1 + h)

= (1 + h)2 – 1

= h2 + 12 + 2(h)(1) – 1

= h2 + 2(h)

Similarly, f(1 + 2h)

= (1 + 2h)2 – 1

= (2h)2 + 12 + 2(2h)(1) – 1

= (2h)2 + 2(2h)

{ (x + y)2 = x2 + y2 + 2xy}

Now take h2 and 2h common in remaining series

Put,

Since,

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

<span lang="EN-USRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2